Isosmotic Macrocation Variation Modulates Mineral Efficiency, Morpho-Physiological Traits, and Functional Properties in Hydroponically Grown Lettuce Varieties (Lactuca sativa L.) - Corrado, Giandomenico; De Micco, Veronica; Lucini, Luigi; Miras-Moreno, Begoña; Senizza, Biancamaria; Zengin, Gokhan; El-Nakhel, Christophe; De Pascale, Stefania; Rouphael, Youssef (Frontiers in Plant Science, 2021)
Management of mineral elements in agriculture is important for their nutritional role for plants and dietary value for humans, sparking interest in strategies that can increase mineral use efficiency and accumulation in plant food. In this work, we evaluated the effects of the isosmotic variations of the concentration on three macrocations (K, Ca, and Mg) in lettuce (Lactuca sativa L.). Our aim was to improve the nutritional components of this valuable dietary source of minerals. Using a full factorial design, we analyzed mineral utilization efficiency, leaf morphology, gas-exchange parameters, phenolic profiles (through UHPLC-QTOF mass spectrometry), and enzymatic activities in two phytochemically diverse butterhead lettuce varieties (red or green). Plants were fed in hydroponics with three nutrient solutions with different ratios of K, Ca, and Mg. The variation of these minerals in the edible product is associated with alterations of the morphology and physiology of the leaves, and of the quality and functional properties of lettuce, with a trade-off between total accumulation and mineral utilization efficiency. Moreover, in non-limiting conditions of nutrient availability, significant mineral interactions were also present. The flexibility of the plant response to the different macrocations’ ratios and the observed large intraspecific variation were adequate to provide mineral-specific phytochemical profiles to the edible product. In particular, the full-red lettuce provided more interesting results regarding the compositional and functional attributes of the leaves.